Effects of acupuncture for nonalcoholic fatty liver disease: A protocol for systematic review and meta-analysis. Issue 47 (20th November 2020) - Zang, Xiaoming; Sun, Mi; Xian, Jin; Yu, Huijuan; Zhang, Xin; Zhang, Changyun; Tan, Qiwen
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is a multisystem disease, which may develop gradually into nonalcoholic steatohepatitis, liver fibrosis, and cirrhosis. As a classical method of traditional Chinese medicine, acupuncture has been used to treat NAFLD in clinical practice. However, there is no systematic review and meta-analysis of acupuncture on NAFLD. There is an urgent need to evaluate the clinical efficacy of acupuncture for NAFLD. Methods: We will perform a comprehensive retrieval in the following electronic databases: MEDLINE, Embase, Cochrane Library Central Register of Controlled Trials, PubMed, Science Citation Index Expanded (Web of Science), Epistemonikos, China National Knowledge Infrastructure (CNKI) database, Wanfang Data Knowledge Service Platform, Chinese Scientific Journals Database (VIP), Chinese Biomedical Literature Service System (SinoMed), and other databases from their inception to October 2020. We will select the qualified studies for data extraction and assess the quality and risk of bias, independently. The meta-analyses will be conducted by using the RevMan 5.3. Results: This study will provide a reliable basis for the treatment of NAFLD with acupuncture. Conclusion: The findings will be an available reference to evaluate whether acupuncture is an effective intervention for patient with NAFLD. OSF registration number: 10.17605/OSF.IO/VFYXH.